Stable heat and particle flux detachment with efficient particle exhaust in the island divertor of Wendelstein 7-X. (10th December 2020) - Schmitz, Oliver; Feng, Y.; Jakubowski, M.; König, R.; Krychowiak, M.; Otte, M.; Reimold, F.; Barbui, T.; Biedermann, C.; Bozhenkov, S.; Brezinsek, S.; Buttenschön, B.; et al.
Abstract: The island divertor concept is an innovative and promising idea to handle heat and particle exhaust in stellarators. At the Wendelstein 7-X (W7-X) stellarator, this divertor concept plays a central role in the device mission to demonstrate reactor relevant plasma confinement for steady-state time scales of up to 30 minutes in the high-performance campaign (OP2) starting in 2022. During the recently concluded first campaign with the inertially cooled island divertor, a large step in the experimental qualification of this divertor concept has been made. In discharges heated with electron cylotron resonance heating of 5−6 MW, central densities in the range of 0.7−1.2 × 10 20 m −3 have been reached in combination with full divertor heat flux detachment. Also, significant neutral gas pressures and neutral compression ratios were shown for the first time in combination with reduced divertor particle flux. The divertor heat loads drop by an order of magnitude from >5 MW m −2 to below 0.5 MW m −2 with increasing density, and substantial compression of neutrals reaching neutral pressure in the sub-divertor volume of >6.0 × 10 −4 mbar was seen. These elevated neutral pressure levels can be obtained and maintained with an up to 80% reduction of the particle fluxes onto the divertor target tiles. This discharge scenario was held stably detached for up to 28 seconds, which is equivalent to several hundred energy confinement times τ E and longer than the time scales for current relaxation. No impurity accumulation was seen at constant Z eff ≍ 1.5 and the stored energy stayed constant at levels of W dia  >  600 kJ. The level of neutral pressure and compression reached in this scenario extrapolates well to the steady-state particle exhaust requirements for high-performance steady-state operation in OP2, in which the fully actively cooled high-heat-flux divertor will be available. An overview of this recently discovered divertor regime is given and the status ofthe physics understanding based on modeling of these regimes with the EMC3-EIRENE code is presented.